Nutritional Cognitive Neuroscience: Innovations for Healthy Brain Aging - Zamroziewicz, Marta K.; Barbey, Aron K. (Frontiers in Neuroscience, 2016)
Nutritional cognitive neuroscience is an emerging interdisciplinary field of research that seeks to understand nutrition’s impact on cognition and brain health across the life span. Research in this burgeoning field demonstrates that many aspects of nutrition – from entire diets to specific nutrients – affect brain structure and function, and therefore have profound implications for understanding the nature of healthy brain aging. The aim of this Focused Review is to examine recent advances in nutritional cognitive neuroscience, with an emphasis on methods that enable discovery of nutrient biomarkers that predict healthy brain aging. We propose an integrative framework that calls for the synthesis of research in nutritional epidemiology and cognitive neuroscience, incorporating: (i) methods for the precise characterization of nutritional health based on the analysis of nutrient biomarker patterns, along with (ii) modern indices of brain health derived from high-resolution magnetic resonance imaging. By integrating cutting-edge techniques from nutritional epidemiology and cognitive neuroscience, nutritional cognitive neuroscience will continue to advance our understanding of the beneficial effects of nutrition on the aging brain and establish effective nutritional interventions to promote healthy brain aging.